Robust Quantification of Cerebrovascular Reactivity using Magnetic Resonance Imaging and Hypercapnic Challenges - Milbourn, Colette Clare (2025)
Pseudocontinuous Arterial Spin Labelling (pCASL) magnetic resonance imaging (MRI) can quantify tissue cerebral blood flow (CBF) in the brain, providing a potential clinical biomarker of brain health. A cerebrovascular reactivity (CVR) response can be induced by increasing blood flow via a vasoactive stimulus, e.g. inhaling carbon dioxide during hypercapnic challenges. The overall aim of this thesis was to validate robust measures of CVR using MRI. Multiple investigations examined blood flow changes, magnetic field effects, pharmacological interventions, and advanced CVR analysis methods.